An exploration of the differences in hip strength, gluteus medius activity, and trunk, pelvis, and lower-limb biomechanics during different functional tasks. Issue 1 (1st January 2020) - Sinsurin, Komsak; Valldecabres, Raul; Richards, Jim
ABSTRACT: The purpose of the study was to explore differences in the coronal biomechanics of the trunk, pelvis, hip, and knee joints, and gluteus medius muscle activity (GMed) during walking and step down from two riser heights. Joint kinematics and kinetics from 20 healthy participants were recorded using a 10-camera Qualisys system and force plates, and GMed EMG was recorded using a Delsys Trigno system. Hip abductor strength was measured using a hand-held dynamometer. Pelvic obliquity and lateral trunk bending excursions were significantly higher in walking than in step-down tasks. Significantly greater knee adduction moments were seen during both step-down tasks compared to level walking with significantly greater GMed activity. However, a significant interaction between side and task was seen for hip adduction moment, with step-down tasks showing lower hip moments than during walking, with greater peak hip moments being more apparent in the dominant limb. This suggests the GMed has a greater stabilizing role during the step-down tasks, although walking required a greater mechanical demand. Health professionals should expect to find less excursion of lateral trunk bending in step-down tasks compared to level walking and consider that GMed has different roles in these two tasks.